2024
DOI: 10.1038/s41586-024-07132-6
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory gamma stimulation promotes glymphatic clearance of amyloid

Mitchell H. Murdock,
Cheng-Yi Yang,
Na Sun
et al.

Abstract: The glymphatic movement of fluid through the brain removes metabolic waste1–4. Noninvasive 40 Hz stimulation promotes 40 Hz neural activity in multiple brain regions and attenuates pathology in mouse models of Alzheimer’s disease5–8. Here we show that multisensory gamma stimulation promotes the influx of cerebrospinal fluid and the efflux of interstitial fluid in the cortex of the 5XFAD mouse model of Alzheimer’s disease. Influx of cerebrospinal fluid was associated with increased aquaporin-4 polarization alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The exact mechanism underlying how rhythmic 40 Hz light flicker alleviates neurological functional deficits is currently under intense discussion and investigation 6 . Existing evidence indicates that 40 Hz light flicker entrain with various brain areas, including the hippocampus, to stimulate responses in hippocampal neural circuits 4 , the circadian clock 37 , the glymphatic contraction 3 , microglial activation 1 , and secretion of selective neurochemical mediators such as adenosine 5,7 . However, these studies have primarily focused on acute and short-term exposure to 40 Hz light flicker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism underlying how rhythmic 40 Hz light flicker alleviates neurological functional deficits is currently under intense discussion and investigation 6 . Existing evidence indicates that 40 Hz light flicker entrain with various brain areas, including the hippocampus, to stimulate responses in hippocampal neural circuits 4 , the circadian clock 37 , the glymphatic contraction 3 , microglial activation 1 , and secretion of selective neurochemical mediators such as adenosine 5,7 . However, these studies have primarily focused on acute and short-term exposure to 40 Hz light flicker.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of our own and others have demonstrated significant beneficial effects of rhythmic 40 Hz light flicker in alleviating cognitive deficits in animal models of AD 13 , stroke 4 , and ASD 5 . While the specific underlying mechanisms vary and are currently under rigorous investigation and debate 6 , several potential pathways have emerged, including the enhancement of mechanisms involved in the clearance of toxic materials 13 , improvement in synaptic connectivity and strength 4 , and increased neurochemical mediators 5,7 . Our human brain electroencephalogram studies have confirmed not only an increase in 40 Hz entrainment in various brain regions but also a substantial alteration in microstates associated with brain functions damaged in AD and stroke patients 8 .…”
Section: Introductionmentioning
confidence: 90%
“…79 As such, the effects of PVN g stimulation may also be mediated by network level effects due to electrical coupling between PVNs 80 or dense recurrent connectivity between cortical regions. 28 There are also reasons to speculate that auditory desensitization after PVN g stimulation may not be directly mediated by synaptic plasticity, as bouts of 40Hz PVN or sensory stimulation have been shown to cause increased cerebral blood flow, 43,81 neurotrophic factor expression, 82 neuropeptide release, 81 glymphatic clearance, 81 and decreased inflammatory responses. 43 Importantly, these effects are linked to stimulation-evoked changes in neural activity and not the direct vasodilation of cortical arterioles by light stimulation, 43 consistent with the fact that no changes were observed in our PVN control stimulation group which received 25% more light exposure over the course of the stimulation compared to the g stimulation group (50 vs. 40 ms of blue light per second).…”
Section: Possible Mechanisms Underlying Sound Dampening Pvn Potentiat...mentioning
confidence: 99%
“…In addition to using drugs or biologics, clearing obstructed glymphatic channels has also been achieved in animal models using mechanical methods such as focused ultrasound treatment in combination with microbubbles (FUS-MB) ( 122 ), and non-invasive neuronal stimulation techniques, such as transcranial magnetic stimulation (TMS) or multisensory stimulation ( 228 , 229 ). A recent study using the 5xFAD AD mouse model showed that treatment with FUS-MB led to enhanced solute Aβ clearance from the brain, first into the CSF space and then into the deep cervical lymph nodes, which correlated with improved memory functions ( 122 ).…”
Section: Considerations In the Study And Clinical Use Of Brain-border...mentioning
confidence: 99%